Conceptual framework of key performance indicator for industralised building system project in Malaysia - Yan, Kim Leong, 1988- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2017